Comparison of the Mechanical Properties Between the Convex and Concave Inner/Apical Surfaces of the Developing Cerebrum - Nagasaka, Arata; Miyata, Takaki (Frontiers in Cell and Developmental Biology, 2021)
The inner/apical surface of the embryonic brain wall is important as a major site for cell production by neural progenitor cells (NPCs). We compared the mechanical properties of the apical surfaces of two neighboring but morphologically distinct cerebral wall regions in mice from embryonic day (E) 12 to E14. Through indentation measurement using atomic force microscopy (AFM), we first found that Young’s modulus was higher at a concave-shaped apical surface of the pallium than at a convex-shaped apical surface of the ganglionic eminence (GE). Further AFM analysis suggested that contribution of actomyosin as revealed with apical-surface softening by blebbistatin and stiffness of dissociated NPCs were both comparable between pallium and GE, not accounting for the differential apical surface stiffness. We then found that the density of apices of NPCs was greater, with denser F-actin meshwork, in the apically stiffer pallium than in GE. A similar correlation was found between the decreasing NPC apices density between E12 and E14 and the declining apical-surface stiffness in the same period in both the pallium and the GE. Thus, one plausible explanation for the observed difference (pallium>GE) in apical surface stiffness may be differential densification of NPC apices. In laser ablation onto the apical surface, the convex-shaped GE apical surface showed quicker recoils of edges than the pallial apical surface did, with a milder inhibition of recoiling by blebbistatin than in pallium. This greater pre-stress in GE may provide an indication for how the initially apically concave wall then becomes an apically convex “eminence”.